The influence of socioeconomic status on academic performance of university students / Muhammad Aris Baharom, Nursyaza Liyana Che Rozilan and Nurdia Azlin Ghazali - Baharom, Muhammad Aris; Che Rozilan, Nursyaza Liyana; Ghazali, Nurdia Azlin (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Socioeconomic status is one of the most explored and debated variables affecting academic performance among educational professionals. The most popular claim is that students’ socioeconomic status affects the quality of their academic performance. The main aim of this study was to investigate the extent to which academic performance of students differs based on socioeconomic status. This study involved 358 students from diploma and degree at UiTM Kampus Seremban. Descriptive survey research design was employed. A self-administered electronic questionnaire was used to obtain data related to socioeconomic status and academic performance of students. Data were analyzed using Descriptive statistics and one-way analysis of variance ANOVA. The results revealed that there is a significant difference in the students’ academic performance between parents’ level of education. Moreover, there is no significant difference in the students’ academic performance between parental income and marital status. This study is crucial for promoting educational equity and improving long-term socio-economic outcomes for individuals, especially students and society as a whole.